Diagnostic Efficacy and Decision-Making Role of Preoperative Endoscopic Ultrasonography in Early Gastric Cancer - Li, Xiao; Zhu, Min; Wang, Yongjun; Niu, Yinglin; Ji, Ming; Li, Peng; Zhang, Shutian (Frontiers in Medicine, 2021)
Objectives Endoscopic ultrasonography (EUS) is the most commonly used method for T staging of early gastric cancer (EGC). However, the studies pertaining to EUS for staging EGC reported widely varied sensitivities and specificities. This study aimed to estimate the overall diagnostic accuracy of EUS for staging the depth of EGCs and to explore the influential factors. Methods We retrospectively reviewed data from 208 consecutive patients with EGC, and all patients underwent EUS for estimating tumor invasion depth, followed by either curative surgery or endoscopic submucosal dissection (ESD). The diagnostic accuracy of EUS was evaluated by comparing the final histologic results of resected specimen. The correlation between accuracy of EUS and characteristics of EGC lesion was analyzed. Results A total of 211 EGC lesions in 208 patients were included. The overall diagnostic accuracy of EUS in assessing the tumor invasion depth of EGC was 55.9%. Multivariate analysis showed that submucosal invasion (OR 2.615; 95% CI 1.203–5.684, P=0.015) was independently associated with misdiagnosis of the depth of EGC and 0-III type lesions (OR 31.495; 95% CI 2.083–476.256, P=0.013) was independently risk factors for over-diagnosis of invasion depth by EUS. However, EUS was only suitable for lesions within absolute indications for endoscopic resection. Conclusions The overall accuracy of EUS in diagnosing invasion depth of EGC was relatively low. Thus, EUS is not necessary routinely for determining the therapeutic strategy for EGC.